Korean masculinities and transcultural consumption : Yonsama, Rain, Oldboy, K-Pop idols - Jung, Sun, 1972- (TransAsia--screen cultures., 2011)
Investigates transcultural consumption of three iconic figures, the middle aged Japanese female fandom of actor Bae Yong-Joon, the Western online cult fandom of the horror film Oldboy, and the Singaporean fandom of the popstar Rain.